A Review Based On Plc For Mixing And Filling Of Liquids” (International Journal of Engineering and Computer Science, 2017)
In today’s fast moving world for survival of company many factors are important such as, cost effective production flexibility of work according in work , production on time etc. In this paper we are going to survey about the liquid mixing and bottle filling process using PLC. The importance of use of PLC is that will allow the mixing of different liquids in desired amount ,the high speed process, accuracy in amount of liquid to be fill into bottles and in any case liquid is any chemical which is dangerous to human health then the mixing and filling both processes are carried out without human touch.